Adverse drug reactions: five historical scandals. (October 2020) - Horwitz, Henrik; Gotfredsen, Ditte Resendal; Christoffersen, Thea
Abstract : Summary: It is estimated that eight percentage of all acute medical admissions are due to adverse drug reactions, and three percentage of all approved new medical entities are later withdrawn from the market due to safety issues. Adverse drug reactions are of public health concern and this paper reviews five selected adverse drug reaction scandals that all caused significant stir and had a huge impact on our way of thinking, drug development and legislation.